Implications on equity in agricultural carbon market projects: a gendered analysis of access, decision making, and outcomes - Lee, J.; Martin A; Kristjanson, Patricia M.; Wollenberg, Eva Karoline (SAGE Publications, 2015)
Carbon market projects have focused on reducing greenhouse gas emissions, often at the expense of achieving sustainable development goals. A central pillar in sustainable development is equity, yet most projects pay little attention to equity implications for underrepresented farmers, especially women. Agricultural carbon market projects that explicitly seek to promote sustainable agricultural land management practices are quickly gaining attention worldwide for their promise to deliver the ‘triple-win’: adaptation, food security, and mitigation. Previous experience with other payment for ecosystem services projects indicate that women often are marginalized and their needs ignored. To address this gap, this case study examined the Kenya Agricultural Carbon Project with a focus on gender equity in access, decision making, and outcomes. Results show that women had less access to joining the project than men, because they did not have the same level of influence in decision making at a household level. At the project level, both men and women had little influence in establishing project requirements and potential benefits, as these were decided upon prior to farmer recruitment. Regarding outcomes, women tended to participate in more project activities, and would in return reap more nonmonetary benefits than men. However, the costs involved in achieving these benefits was nontrivial: women's farm labor time increased significantly due to the substantial time and effort required to implement sustainable agricultural land management practices. If agricultural soil carbon market projects are to achieve better outcomes by addressing equity issues, they need to pay special attention to gender and the differing needs of farmers—male, female, young, old, poor, and less poor—by involving them at the project design stage. Our findings show the importance of additional project benefits unrelated to carbon income for addressing the requirements of equity perceived by both the implementing agency and women themselves.